2019
DOI: 10.1002/lno.11304
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between ultraviolet radiation exposure and phosphorus limitation in the marine nitrogen‐fixing cyanobacteria Trichodesmium and Crocosphaera

Abstract: Increased stratification and mixed layer shoaling of the surface ocean resulting from warming can lead to exposure of marine dinitrogen (N2)‐fixing cyanobacteria to higher levels of inhibitory ultraviolet (UV) radiation. These same processes also reduce vertically advected supplies of the potentially limiting nutrient phosphorus (P) to N2 fixers. It is currently unknown how UV inhibition and P limitation interact to affect the biogeochemical cycles of nitrogen and carbon in these biogeochemically critical micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 86 publications
4
16
0
Order By: Relevance
“…Thus, it seems possible that in-situ PAR values would not photoinhibit these DDA strains. However, damaging effects by solar UV wavelengths (Zhu et al, 2020) require further examination. Follett et al (2018) and Inomura et al (2020) utilized H. hauckii DDA growth rates extracted from Pyle (2011) for modeling applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it seems possible that in-situ PAR values would not photoinhibit these DDA strains. However, damaging effects by solar UV wavelengths (Zhu et al, 2020) require further examination. Follett et al (2018) and Inomura et al (2020) utilized H. hauckii DDA growth rates extracted from Pyle (2011) for modeling applications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems possible that in-situ PAR values would not photoinhibit these DDA strains. However, damaging effects by solar UV wavelengths ( Zhu et al, 2020 ) require further examination.…”
Section: Discussionmentioning
confidence: 99%
“…In the marine diazotroph Trichodesmium, UV radiation reduces rates of photosynthesis, N 2 fixation, and growth (Cai X. et al, 2017), though moderate or low levels of UV-A may be stimulating. Another recent study showed that growth, N 2 fixation, and CO 2 fixation rates of the Trichodesmium strain IMS 101 and Crocosphaera WH0005 were both negatively affected by UV-B exposure (Zhu et al, 2019). This inhibition was much greater for Trichodesmium IMS 101, which fixes N 2 during the day, than for Crocosphaera, which fixes N 2 only during the night; however, another Trichodesmium isolate (GBR) was much more resistant to UV-B inhibition (Zhu et al, 2019).…”
Section: Interactions Between Oa Effects and Nitrogen Fixation And Wimentioning
confidence: 99%
“…Another recent study showed that growth, N 2 fixation, and CO 2 fixation rates of the Trichodesmium strain IMS 101 and Crocosphaera WH0005 were both negatively affected by UV-B exposure (Zhu et al, 2019). This inhibition was much greater for Trichodesmium IMS 101, which fixes N 2 during the day, than for Crocosphaera, which fixes N 2 only during the night; however, another Trichodesmium isolate (GBR) was much more resistant to UV-B inhibition (Zhu et al, 2019). To the best of our knowledge, however, nothing has been documented on the interactive effects of OA and UV radiation on marine diazotrophs.…”
Section: Interactions Between Oa Effects and Nitrogen Fixation And Wimentioning
confidence: 99%
“…Modified F/2 medium (100 µM total nitrogen, 100 µM silicate, 6 µM phosphate; Guillard and Ryther, 1962;Guillard, 1975) was made using natural seawater filtered through an ultrafiltration water purifier (MUF1580-2T, Midea, China), autoclaved, and bubbled with air filtered through a 0.22 µm PVD syringe filter (Membrane Solutions, Nantong) to equilibrate with ambient atmospheric gas concentrations. Quartz culture bottles were used to allow UVB wavelengths to pass through (Zhu et al, 2020).…”
Section: Culture Conditionsmentioning
confidence: 99%